Activites of Hakoba Zavriyan during the resumption of the Armenian question (1912-1914) - Yeranosyan, Manyak (History and Culture, 2023)
In Armenian and world historiography, enough work has been done in the direction of studying the issue of Armenian reforms in 1912-1914, the policies of different states and the activities of individuals, however, the activities of the well-known politician, Dr. Hakob Zavriyan,s activity in the mentioned years were not the subject of a separate study, although Over the past years, some authors, as well as us, have found in the archives and published a number of documents that remained outside scientific circulation.In the context of the processes taking place at the global and national levels, the article presents the activities of Hakob Zavriyan in the national, but especially the international arena to open the Armenian question in the specified period before the signing of the reform agreement.In our opinion, he did significant organizational work at the national level to unite different layers of Armenians and develop reform programs. And in the international arena, A. Zavriyana promoted the issue of reforms, especially in his numerous contacts with the governments of Russia and Germany, trying to give their policies a pro-Armenian direction.
Keywords: Armenian question; reforms; A. Zavriyan; S. Sazonov; M. Girs; Dashnaktsutyun; Western Armenia; Ottoman Empire; Constantinople; Russia